THE INFLUENCE OF INTEREST IN LEARNING ON THE LEARNING ACHIEVEMENT OF SOCIAL SCIENCE SUBJECTS - Supriyadi, Supriyadi (International Journal of Business, Law, and Education, 2022)
This research aims to reveal whether there is an influence of interest in learning on students' learning achievement in social studies subjects. The research method used is associative quantitative methods. The sampling technique used random sampling with a sample size of 84 students at AL-Ikhlas Middle School Bekasi. Research data was obtained using valid and reliable instruments. The data analysis used is regression analysis of Y and This means Ho is rejected. Thus, the correlation coefficient X and Y is meaningful or significant. Meanwhile, the coefficient of determination R Square = 0.242, which means that 24.2% of the variation in the Social Sciences Learning Achievement variable can be influenced by Learning Interest. The conclusion of the research results reveals that there is an influence of student learning achievement on interest in learning, this can be seen from the regression equation Y = 48.769 + 0.445X, meaning that the Y score can be predicted using the linear equation mentioned above. From the analysis results t hit = 5,250 and p-value = 0.000/2 = 0 < 0.05 or Ho is rejected. Thus, interest in learning has a positive effect on learning achievement in social science subjects.